Pneumoperitoneum and Pneumatosis cystoides intestinalis, a dangerous mixture. A case report - Moyon, Fernando X. (Int J Surg Case Rep, 2020)
BACKGROUND: Pneumatosis cystoides intestinalis (PCI) is a rare condition characterized by gas infiltration into the intestine wall. When gas is seen in the intestinal wall, it is usually a sign of bowel wall infarction and a surgical emergency; therefore, an adequate differentiation of benign and urgent conditions of pneumatosis intestinalis is necessary to prevent misdiagnosis and inadequate therapies. CASE PRESENTATION: We present the case of a 79-year-old male with past medical history of Alzheimer’s, cholecystectomy, and umbilical hernia. PCI was identified, and conservative therapy was started. Since the patient's pain persisted, a complication was suspected, and surgery was decided. After successful treatment, the patient completely recovered. CONCLUSION: There are many benign and life-threatening causes of pneumatosis intestinalis, the imaging appearance of both may look very similar. Therefore, clinical history, physical examination, and laboratory test results are the best indicators of whether it is due to a benign or life-threatening cause. PCI must be managed with a multidisciplinary team of clinicians, radiologists, and surgeons to achieve better results for our patients.